PENCABUTAN SERTIPIKAT HAK MILIK AKIBAT TUMPANG TINDIH DALAM PROGRAM PENDAFTARAN TANAH SISTEMATIK LENGKAP DI KABUPATEN BOGOR - Anwarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research analyzes the revocation of a Freehold Title Certificate due to land overlap within the Integrated Systematic Land Registration program, based on the Bandung Administrative Court Decision Number 15/G/2018/PTUN.BDG. The case originated when the Defendant the Head of the Bogor Regency Land Office issued SHM Number 4611/Karadenan in the name of Caca Suarca (issued on December 21, 2017). This title was found to overlap with the Right to Build Certificate (HGB) Number 329/Karadenan held by the Plaintiff, PT Star Tjemerlang (based in West Jakarta)—which had been issued in 1999. Employing a normative legal research method, this study evaluates the application of the General Principles of Good Governance.